2021
DOI: 10.1002/chem.202103886
|View full text |Cite
|
Sign up to set email alerts
|

Gold N‐Heterocyclic Carbene Catalysts for the Hydrofluorination of Alkynes Using Hydrofluoric Acid: Reaction Scope, Mechanistic Studies and the Tracking of Elusive Intermediates

Abstract: An efficient and chemoselective methodology deploying gold-N-heterocyclic carbene (NHC) complexes as catalysts in the hydrofluorination of terminal alkynes using aqueous HF has been developed. Mechanistic studies shed light on an in situ generated catalyst, formed by the reaction of Brønsted basic gold pre-catalysts with HF in water, which exhibits the highest reactivity and chemoselectivity. The catalytic system has a wide alkyl substituted-substrate scope, and stoichiometric as well as catalytic reactions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 83 publications
0
25
1
Order By: Relevance
“…However, no distinct anion influence was observed, [23] on using AgSbF 6 and AgOTf instead of AgBF 4 with [Au(Cl)(SIPr)] as well as [Au(I)(SPhos)] ( 19 ) as catalytic precursors (entries 9–12). The observed yields were mostly lower when compared the literature, [3a,5b,d,e,6b] but higher than reported for [Au(Cl)(PPh 3 )]/AgBF 4 , which showed only a stoichiometric conversion [5a] …”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…However, no distinct anion influence was observed, [23] on using AgSbF 6 and AgOTf instead of AgBF 4 with [Au(Cl)(SIPr)] as well as [Au(I)(SPhos)] ( 19 ) as catalytic precursors (entries 9–12). The observed yields were mostly lower when compared the literature, [3a,5b,d,e,6b] but higher than reported for [Au(Cl)(PPh 3 )]/AgBF 4 , which showed only a stoichiometric conversion [5a] …”
Section: Resultscontrasting
confidence: 57%
“…After formation of the vinyl species, the protodeauration should provide the hydrofluorinated compound and the catalytic cycle is completed (Scheme 5). In a recent paper regarding the Au(I) catalyzed hydrofluorination of terminal alkynes with aqueous HF, cationic complexes have also been postulated as intermediates [6b] . In addition to mononuclear intermediates, binuclear species involving Au(I) alkynyl complexes, were proposed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NBO analysis reveals partial C–H bond formation and C–Au bond breaking in the transition state, while IRC calculations are consistent with the association of the resulting charged fragments {Au(IPr)} + and X – occurring afterward. 59 64 The overall transformation is calculated to be exergonic (Δ G ° rxn = −22.6 kcal mol –1 ), with the S N Ar step being turnover-limiting.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that attempted crystal growth of a gold bifluoride complex in a glass vessel led to the formation of an undesired complex bearing a pentafluorosilicate counterion. 38 The desired bifluoride complex was successfully obtained by instead growing the crystals in a plastic vessel.…”
Section: Container-dependent Stability Of Organofluorine Compoundsmentioning
confidence: 99%